PENERAPAN METODE ADAPTIVE NEURO FUZZY INFERENCE SYSTEM UNTUK PENENTUAN SISWA PENERIMA KARTU INDONESIA PINTAR - Jefina Tri Kumalasari (Yayasan Akrab Pekanbaru, 2019)
Abstract The Smart Indonesia Card is part of President Joko Widodo's policy for vulnerable and poor poor families who want to provide good education to children without fees. The age of the child is borne by the cost of education is from the age of 6 to 18 years. With this KIP program, it is expected that the dropout rate it can go down drastically. Subjectivity can occur in decision making as a result of inaccurate data. So that there is unclear decision making based on the description, so we need a system to facilitate the determination of students who are entitled to use the Indonesia Smart Card where decisions are at school, the researchers use the Adaptive Neural Fuzzy Inference System (ANFIS) method to create a system after inputting data on certain variables which will result in whether students have the right to be considered for KIP or not. Tests show that the type of membership function with a hybrid algorithm with the input parameter